Association of sleep quality and internet addiction among the medical students - Nagori, Nidhi; Vasava, Kinjal; Vala, Ashok U. Vala U.; Ratnani, Imran J. (International Journal of Research in Medical Sciences, 2019)
Background: The side effects of Internet overuse have been emerging progressively causing the emergence of a problem that is defined as internet addiction or problematic internet use. It also disrupts the sleep wake cycle so adversely affecting quality of sleep. This study is a preliminary step toward understanding the effect of internet addiction on sleep quality among medical college students in India. Methods: This was an observational, cross-sectional, single-centred, and self-assessable. Questionnaire based study administrated among 525 consenting medical students. The participants were assessed by proforma containing demographic details, variables related with internet use, questionnaires of IAT (Internet Addiction Test for Internet Use) and PSQI (Pittsburgh Sleep Quality Index for Sleep quality. Statistical data were analysed by Graph Pad InStat version 3.06 using Chi–square test and Mann-Whitney test. Results: There were 9.3% of all participants were considered problematic internet users with frequency of internet addiction 0.9%. Participants with problematic internet use are likely to have poor sleep quality (p<0.0001). 23.8% of all participants had poor sleep quality and 76.2% of the students had good quality of sleep. Participants with poor quality of sleep were having high IAT scores in comparison to participants with good quality of sleep. Severity of poor sleep quality is positively correlated with internet addiction (r2=0.233, p<0.0001). Conclusions: Participants with problematic internet use were more likely to have poor quality of sleep and vice a versa.